2013
DOI: 10.1111/sji.12099
|View full text |Cite
|
Sign up to set email alerts
|

HBcAg‐Specific IL‐21‐Producing CD4+ T Cells are Associated with Relative Viral Control in Patients with Chronic Hepatitis B

Abstract: Function exhaustion of specific cytotoxic CD8+ T cell in chronic virus infection partly results from the low levels of CD4 help, but the mechanisms by which CD4 help T cell required to control hepatitis B virus infection are not well understood. In this study, we investigated the role of interleukin-21-producing CD4+ T cell response in viral control of hepatitis B virus infection. HBcAgspecific interleukin-21-producing CD4+ T cells in blood were detected in patients with hepatitis B virus infection. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 25 publications
1
18
1
2
Order By: Relevance
“…22 Although IL-21 levels in chronic hepatitis B (CHB) and IC patients were comparable, there was a higher frequency of IL-21 1 CD4 1 T or IL-21 1 CXCR5 1 CD4 1 T cells in the IC than the CHB group after either nonspecific (phorbol myristate acetate/ionomycin) or specific (HBV core antigen or peptides) stimulation. 22,23 However, similar observations were not obtained in a recent study by Li et al 24 This discrepancy may be attributed to patient selection, as viral load or viral antigens could influence the HBV-specific CD4 1 T-cell response in CHB patients. Interestingly, Li et al found a significantly elevated frequency of HBcAg-specific IL-21 1 CD4 1 T cells in patients with acute hepatitis B (AHB).…”
Section: Function Of Il-21 In Cellular Immune Responsescontrasting
confidence: 48%
See 2 more Smart Citations
“…22 Although IL-21 levels in chronic hepatitis B (CHB) and IC patients were comparable, there was a higher frequency of IL-21 1 CD4 1 T or IL-21 1 CXCR5 1 CD4 1 T cells in the IC than the CHB group after either nonspecific (phorbol myristate acetate/ionomycin) or specific (HBV core antigen or peptides) stimulation. 22,23 However, similar observations were not obtained in a recent study by Li et al 24 This discrepancy may be attributed to patient selection, as viral load or viral antigens could influence the HBV-specific CD4 1 T-cell response in CHB patients. Interestingly, Li et al found a significantly elevated frequency of HBcAg-specific IL-21 1 CD4 1 T cells in patients with acute hepatitis B (AHB).…”
Section: Function Of Il-21 In Cellular Immune Responsescontrasting
confidence: 48%
“…Moreover, HBcAg-specific CD4 1 T cells derived IL-21 from patients with AHB could enhance IFN-c and perforin expression by CD8 1 T cells from CHB patients. 24 These data indicated that HBcAg-specific IL-21-producing CD4 1 T-cell responses could promote the antiviral activity of CD8 1 T cells through IL-21 signaling. Notably, IL-21 in vitro could sustain the survival and function of HBc18-27-specific CD8 1 T cells in this study; while Ren et al 25 reported that the addition of IL-21 in vitro could partially restore the function of HBV-specific CD8 1 T-cell responses in HBV/HIV-1-coinfected patients, but not in HBV-monoinfected patients.…”
Section: Function Of Il-21 In Cellular Immune Responsesmentioning
confidence: 82%
See 1 more Smart Citation
“…Thus, IL-21 may be part of an effective hepatic immune response to HBV in an age-dependent manner. Furthermore, IL-21 may also facilitate HBeAg seroconversion in HBeAg-positive patients, which may contribute to individualization of antiviral therapy (11,18). Our previous study also found that the frequency of IL-21-secreting CD4 + T-cells was increased in patients with acute HBV infection (5).…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, antigen-specific CD4 + Tcells secreting IL-21 sustained maintenance and function of specific CD8 + T-cell response, which eventually controls the chronic lymphocytic choriomeningitis virus (LCMV) infection (7,8,36). Thus, IL-21 could be a new therapeutic target for chronic viral infectious diseases. Recent studies have also demonstrated that IL-21 contributes to the inhibition of viral replication and hepatitis B e antigen seroconversion in chronic hepatitis B (11,13,18). Thus, we hypothesized that IL-21 could regulate the HBVspecific immune response in vivo.…”
Section: Introductionmentioning
confidence: 93%